2018
DOI: 10.1016/j.jcf.2017.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and reproductive health care utilization and preferences reported by young women with cystic fibrosis

Abstract: Young women with CF report low rates of SRH care utilization and desire SRH discussions in the CF setting. Interventions should target improved SRH care delivery and encourage patient-provider communication around SRH in the CF care setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 26 publications
0
46
0
Order By: Relevance
“…While research in CF has demonstrated an essentially neutral impact of pregnancy on health , the data indicate that individuals with CF lack important CF‐specific reproductive health knowledge . Women with CF have exhibited limited awareness and misconceptions of the physical and psychosocial implications of pregnancy and parenthood with this chronic illness; they have also described inadequacies of reproductive health communication from CF providers, including the delayed introduction of reproductive health education, as well as disheartening disapproval of childbearing by CF providers . The only known study on CF‐related reproductive health education including men suggests that deficiencies also exist in education from CF care teams on these topics …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While research in CF has demonstrated an essentially neutral impact of pregnancy on health , the data indicate that individuals with CF lack important CF‐specific reproductive health knowledge . Women with CF have exhibited limited awareness and misconceptions of the physical and psychosocial implications of pregnancy and parenthood with this chronic illness; they have also described inadequacies of reproductive health communication from CF providers, including the delayed introduction of reproductive health education, as well as disheartening disapproval of childbearing by CF providers . The only known study on CF‐related reproductive health education including men suggests that deficiencies also exist in education from CF care teams on these topics …”
Section: Introductionmentioning
confidence: 99%
“…6,12,13 Women with CF have exhibited limited awareness and misconceptions of the physical and psychosocial implications of pregnancy and parenthood with this chronic illness; they have also described inadequacies of reproductive health communication from CF providers, including the delayed introduction of reproductive health education, as well as disheartening disapproval of childbearing by CF providers. 6,12,14,15 The only known study on CF-related reproductive health education including men suggests that deficiencies also exist in education from CF care teams on these topics. 13 The few published studies related to parenting with CF have demonstrated that individuals with CF face conflicting recommendations from CF providers, [16][17][18] difficulty balancing responsibilities, 17,18 shifting priorities, [17][18][19] coping with parental stress in the context of illness, 18,20 and guilt about the impact of illness on children.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study from the U.S. National Survey for Family Growth found that contraception counseling was not universally performed for young women during clinic visits related to SRH . Adolescent and young adult women with CF report that SRH is rarely discussed as part of their routine healthcare . Similarly, patient‐provider communication around other important, yet sensitive, health topics, such as advance care planning and prognosis, has been shown to be lacking in CF care …”
Section: Discussionmentioning
confidence: 99%
“…In a recent survey of 15‐24 years old women with CF, one third perceived pubertal delay compared to their peers, nearly one in six reported experiencing urinary incontinence and/or sexual dysfunction, and half had had a yeast infection . In addition, compared to the general United States (U.S.) population, young women with CF were significantly less likely to have ever used contraception or received contraceptive counseling, obtained STI or pregnancy testing, or undergone cervical screening (Pap smears and/or pelvic exams) . Unfortunately, despite these significant gaps in comprehensive care, SRH is not addressed in a systematic way in the CF clinic .…”
Section: Introductionmentioning
confidence: 99%
“…While 72% reported discussing puberty or menstruation with their CF providers, only 1/3rd had discussed sexual activity or contraception. They expressed interest in discussing fertility and pregnancy . In another study, women with CF were found to have similar sexual experiences but had gaps in sexually transmitted infection and contraception care and experienced more SRH related concerns such as delayed puberty, urinary incontinence, yeast infections, and sexual dysfunction .…”
Section: Patient‐reported Outcomes/prioritiesmentioning
confidence: 97%